2021
DOI: 10.3390/su13169253
|View full text |Cite
|
Sign up to set email alerts
|

“This Is the Story of Community Leadership with Political Backing. (PM1)” Critical Junctures in Paralympic Legacy: Framing the London 2012 Disability Inclusion Model for New Global Challenges

Abstract: The London 2012 Paralympic Games was called “the most successful Paralympic Games ever” (by the then-President of the IPC), and it saw more athletes from more countries than ever before compete and become global heroes for the first time in a redeveloped part of East London which also hosted “the most accessible Olympic Games ever” that summer. However, the model used to design and deliver disability inclusion for London 2012, and its legacy, has never been explicitly written up. This paper presents new primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Simply resolving issues with accessibility by applying local laws and resources will likely not be sufficient to resolve inclusion. Previous studies have demonstrated that empowering leaders within the community to foster inclusive opportunities for people with disabilities can be achieved through several relevant strategies, such as the creation of sustainable relationships and supportive networks, joint problem solving, welcoming disruption, and community-led objectives [18][19][20][21][22]. These methods should align with the Social Model of Disability, where the focus or blame is not on the person with a disability that has an impairment that directly prevents them from participation, but instead places the blame on a society that socially isolates and oppresses [23].…”
Section: Discussionmentioning
confidence: 99%
“…Simply resolving issues with accessibility by applying local laws and resources will likely not be sufficient to resolve inclusion. Previous studies have demonstrated that empowering leaders within the community to foster inclusive opportunities for people with disabilities can be achieved through several relevant strategies, such as the creation of sustainable relationships and supportive networks, joint problem solving, welcoming disruption, and community-led objectives [18][19][20][21][22]. These methods should align with the Social Model of Disability, where the focus or blame is not on the person with a disability that has an impairment that directly prevents them from participation, but instead places the blame on a society that socially isolates and oppresses [23].…”
Section: Discussionmentioning
confidence: 99%
“…Identifying an operational approach to delivery with similar complexity toward a disability inclusion aim is challenging. For another study, we mapped the London 2012 Disability Inclusion approach, using a Delphi methodology with expert testimony [23] as an example, and found 12 steps of the operational activity necessary to deliver the complex intervention, as shown in Figure 1. This is helpful to consider as context.…”
Section: Disability Justice and Wider Justice Framingmentioning
confidence: 99%
“…The delivery of disability inclusion in the London 2012 Paralympic Games program is considered one of the most challenging and successful disability inclusion interventions [23]. It should be acknowledged that there is much to separate it from global work on AT delivery: a largely national rather than global locus of leadership (though with global stakeholders, such as the International Paralympic Committee and delivery partners); and the delivery of a discrete program of events, which together create a megaevent, compared with a continuous program of activity.…”
Section: Considering At In the Light Of The London 2012 Disability In...mentioning
confidence: 99%
See 2 more Smart Citations